Changes in blood ion levels after removal of metal-on-metal hip replacements. (June 2014) - Durrani, Salim K; Noble, Philip C; Sampson, Barry; Panetta, Therese; Liddle, Alexander D; Sabah, Shiraz A; Chan, Newton K; Skinner, John A; Hart, Alister J
<x xml:space="preserve">Abstract</x> Background and purpose — In patients with metal-on-metal (MoM) hip prostheses, pain and joint effusions may be associated with elevated blood levels of cobalt and chromium ions. Since little is known about the kinetics of metal ion clearance from the body and the rate of resolution of elevated blood ion levels, we examined the time course of cobalt and chromium ion levels after revision of MoM hip replacements. Patients and methods — We included 16 patients (13 female) who underwent revision of a painful MoM hip (large diameter, modern bearing) without fracture or infection, and who had a minimum of 4 blood metal ion measurements over an average period of 6.1 (0–12) months after revision. Results — Average blood ion concentrations at the time of revision were 22 ppb for chromium and 43 ppb for cobalt. The change in ion levels after revision surgery varied extensively between patients. In many cases, over the second and third months after revision surgery ion levels decreased to 50% of the values measured at revision. Decay of chromium levels occurred more slowly than decay of cobalt levels, with a 9% lag in return to normal levels. The rate of decay of both metals followed second-order (exponential) kinetics more closely than first-order (linear) kinetics. Interpretation — The elimination of cobalt and chromium from the blood of patients who have undergone revision of painful MoM hip arthroplasties follows an exponential decay curve with a half-life of approximately 50 days. Elevated blood levels of cobalt and chromium ions can persist for at least 1 year after revision, especially in patients with high levels of exposure.